Kajian Pengembangan Desa Wisata Berbasis Komunitas Di Desa Sidorejo Kabupaten Kediri - Trimurti Ningtyas; Binti Mutafarida; Indah Rahayu Puspitasari (Universitas Dr. Soetomo Surabaya, 2022)
This article discusses a form of village development planning in the field of tourism. This study on the development of a tourist village has become an important part of the government's efforts to increase the village's economic independence. The existence of a village fund program from the government can be utilized as part of the first source of funding for the development of tourism villages in Sidorejo Village, Kediri Regency. This research uses the CBR (Community Based Research) method so that people's participation in the community can be seen clearly. This study illustrates that socialization and deliberation as a form of community action. The socialization was carried out by involving officials and communities in Sidorejo Village. While deliberations are held with the apparatus to bridge the wishes of the people of Sidorejo Village. The end result is that the community is involved starting from the village tourism development planning process, namely in mapping village land that will be used, physical development planning and funding, as well as operational concepts ranging from the allocation of Micro, Small and Medium Enterprises (MSMEs) to the procurement of the informal economy sector such as parking lots and motorcycle taxis. There is community participation as evidence that the results of this study can be followed up for the process of further policy formulation which is to determine the budget plan of the village government in the following year with the priority of developing tourist villages in Sidorejo Village, Kediri Regency.